Let $a= t^0 \lt t^1 \lt … \lt t^N =b$ a random division of $[a,b]$ space where $h_n = t^{n+1} - t^n$ for $n=0,1,…,N-1$.

We consider the initial value problem $$ y'(t)=f(t,y(t))\text{ for } a \le t \le b \ \&\ y(a)= y_0 $$

Function $f \in ( C[a,b]×R )$ and satisfies the Lipschitz condition with constant $L>0$ for $a \le t \le b$

In addition, $M=\max|y''(t)|$ & $h=\max h_n $ for $0 \le n \le N-1$

Show that $| ε_n | \le M {h\over2L} [ e^{L(b-a)} -1]$

We define $ε_n =y( t^n )- y^n$ the error of Euler's method with variable step $h_n$ and by applying this method to the problem we conclude to this:

\begin{align} | ε_{n+1} | &\le (1+ h_n L)| ε_n | + h_n {h\over2} M \\ &\le M {h\over2} \Bigl[ h_n +(1+ h_n L) h_{n-1} +(1+ h_n L)(1+ h_{n-1} L) h_{n-2} + \\&\qquad\qquad…+(1+ h_n L)(1+ h_{n-1} L)\cdots(1+ h_1 L) h_0 \Bigr] \\ &\le M {h\over2} \Bigl[ h_n + e^{L(t^{n+1}-t^n)} ( t^n - t^{n-1} )+ e^{L(t^{n+1}-t^{n-1})} ( t^{n-1} - t^{n-2} )+ \\&\qquad\qquad…+ e^{L(t^{n+1}-t^1)} ( t^1 - t^0 )\Bigr] \\ &\le M {h\over2} \Bigl[ h_n + \int_{t^{n-1}}^{t^n} e^{L(t^{n+1}-s)} ds + \int_{t^{n-2}}^{t^{n-1}} e^{L(t^{n+1}-s)} ds + \\&\qquad\qquad…+ \int_{t^0}^{t^1} e^{L(t^{n+1}-s)} ds\Bigr] \\ &= M {h\over2} \Bigl[ h_n + \int_{t^0}^{t^n} e^{L(t^{n+1}-s)} ds\Bigr] \end{align}

At this point I have been stuck because I don't know how to get rid of the ' $h_n$ ' I would appreciate any help ..How could I continue in order to show this? Thanks in advance!!

  • $\begingroup$ Please change your formula salad into readable mathjax/Latex using only one math environment per formula, using align environment for the large formula block at the bottom,... $\endgroup$ – Dr. Lutz Lehmann Mar 25 '16 at 15:44
  • $\begingroup$ I have to admit that you've been very polite but it was my first attempt to write in mathjax and certainly I didn't nail it... Although I can't see something unreadable here... so except "my formula salad" if you had something else to add about the problem, you 'd help me a lot! thanks $\endgroup$ – kaithkolesidou Mar 25 '16 at 16:10
  • $\begingroup$ See math.stackexchange.com/a/1696107/115115 for the idea for the standard treatment of this problem. $\endgroup$ – Dr. Lutz Lehmann Mar 25 '16 at 16:26
  • $\begingroup$ @kaithkolesidou - you don't need to split every single item into separate $ $ pairs. It really looks better and is a LOT easier to read if you just do an entire fomula instead of bits and pieces. For example: $$a=t^0 \lt t^1\lt \ldots \lt t^N =b$$ gives $$a=t^0 \lt t^1\lt \ldots \lt t^N =b$$ instead of "a=$t^0$ $\lt$ $t^1$ $\lt$ ......$\lt$ $t^N$ =b" $\endgroup$ – Paul Sinclair Mar 25 '16 at 16:26
  • $\begingroup$ @LutzL the ex. gives certain steps we should follow in order to achieve the final inequality, and the point i've stopped it's the last given step.. if i calculate the integral then i conclude to the above inequality BUT the hn is stil there... $\endgroup$ – kaithkolesidou Mar 25 '16 at 16:38

Just use $$ h_n=e^{L(t^{n+1}-t^{n+1})}·(t^{n+1}-t^n) \le \int_{t^n}^{t^{n+1}}e^{L(t^{n+1}-s)} $$ to get to $$ \int_{t^0}^{t^{n+1}}e^{L(t^{n+1}-s)}ds=\frac1L\left(e^{L(t^{n+1}-t^0)}-1\right). $$

  • $\begingroup$ yeeeees you're right... thank you very very much for your help and for your time!! $\endgroup$ – kaithkolesidou Mar 25 '16 at 16:52

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.